A COMPARATIVE ANALYSIS OF THE FOUR SCORE VERSUS THE GCS SCALE IN PREDICTING OUTCOMES IN CRITICALLY-ILL PATIENTS IN AN INTENSIVE CARE UNIT IN PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Background: Timely and accurate neurological evaluation is crucial for intubated patients in the intensive care unit (ICU). Use of the GCS scale is standard across ICUs, although it has several limitations. Scoring systems such as Full Outline of Unresponsiveness (FOUR) can also be used to assess intubated patients. We perform a study comparing the accuracy of the FOUR score versus the GCS scale in predicting likelihood of successful extubation, and other clinical outcomes, in critically-ill patients at a tertiary care hospital in Pakistan.Objective: This study aims to compare the accuracy of FOUR score versus the GCS scale (when administered by non-neurologist ICU clinicians) for predicting extubation success, ICU length of stay (ICU-LOS), and other clinical outcomes.Methods: This study was conducted in a prospective cohort study design at the Aga Khan University Hospital, Pakistan (September 2024 to April 2025). We enrolled adults (over 18 years) who were intubated, and in the ICU. GCS and FOUR scores were recorded by ICU fellows, consultants, and trained nurses at the ‘time of admission’ and ‘prior to extubation’. Patients on neuromuscular blockade were excluded. Demographic data, comorbidities, ICU-LOS, and extubation success (defined as no reintubation for 48-72 hours) were recorded. Statistical analysis was performed using chi-square test, t-test, correlation coefficients, and receiver operating characteristic (ROC) curves.Results: The study enrolled 160 patients, 66.9% of whom were male, average age of 51.1 ± 17.3 years. Extubation success rate was 92.5%. Diagnostic accuracy of the ‘pre-extubation FOUR score’ versus ‘GCS scale’ were marginally different and not statistically significant (AUC = 0.63 vs 0.59, p > 0.05). Both FOUR and GCS had a high positive predictive value (PPV), 94.7% and 94.0%, respectively, but a low negative predictive value (NPV); 12.8% and GCS: 11.6%, respectively. Patients with extubation failure had significantly shorter ICU-LOS.Conclusion: Both FOUR and GCS scoring systems provided predictive accuracy for extubation success, with slightly better performance for the FOUR score. Both scoring systems provided weak predictive value for failure. The use of the FOUR score can augment the neurological assessment of ICU patients, especially in units with limited neurology resources and high patient volumes.